Specifics of Translating Osteopathic Terminology from English into Latvian - Irina Kaļiņina (Baltic Journal of English Language, Literature and Culture)
The present article explores the complex issue of translation in the field of biodynamic osteopathic terminology. Due to the status of this discipline in Latvia, terms in the source language (English) still need to be transposed into Latvian, implementing the process of secondary term creation. The research examines community-generated translation practices and provides an overview of the resulting situation. The principles of terminological work are based on the communicative and frame-based theories of terminology, with the grounding principles of the General Theory of Terminology (GTT). The methodology includes qualitative and quantitative analysis of term translations obtained from 7 respondents, based on a corpus of 229 terms extracted from course books and didactic CDs in the field of biodynamics in osteopathy. The resulting data on user-generated translation practices can serve as a basis for further exploration of the given terminology in a more prescriptive key.